LETM1 Knockdown Promotes Autophagy and Apoptosis Through AMP-Activated Protein Kinase Phosphorylation-Mediated Beclin-1/Bcl-2 Complex Dissociation in Hepatocellular Carcinoma - Baoyong Zhou; Changhong Yang; Xiong Yan; Zhengrong Shi; Heng Xiao; Xufu Wei; Ning Jiang; Zhongjun Wu (Frontiers in Oncology, 2021)
Leucine zipper/EF hand-containing transmembrane-1 (LETM1) is an inner mitochondrial membrane protein that has been reported to be involved in many primary tumors and may regulate many biological processes. However, the biological role and molecular mechanism of LETM1 in the progression of hepatocellular carcinoma (HCC) remain largely unknown. In this study, we found that LETM1 was highly expressed in HCC tissues and cell lines and that higher LETM1 expression was associated with a lower overall survival rate in HCC patients. In addition, knockdown of LETM1 inhibited proliferation and enhanced apoptosis and autophagy in the Huh 7 and QGY-7701 liver cancer cell lines. Mechanistically, knockdown of LETM1 dissociated the Beclin-1/Bcl-2 complex through phosphorylation of AMPK and Bcl-2. These results demonstrated that LETM1 is involved in the development of HCC and could be a novel therapeutic target in HCC.